On the effectiveness of metal particle combustion performance and implications to Martian missions. (15th June 2023) - Tran, Quan; Vaz, Neil; Pantoya, Michelle L.; Altman, Igor
Highlights: Magnesium particles show limited combustion completeness. Vapor phase reactions condense oxide products on particle surface. Condensation on surface encapsulates unreacted metal. Unburnt and encapsulated metal core limits further oxidation. Abstract: There is a natural abundance of carbon dioxide in the Martian atmosphere that can oxidize magnesium fuel. Combustion of magnesium carried from Earth is considered as a potential propulsion process for Mars Ascent Vehicles. Other space exploration missions would benefit from magnesium combustion and thus sparked motivation to resolve puzzles in existing models for metal combustion. Harnessing all the chemical potential energy available in a metal particle will optimize power generation capabilities and payload demands. Here we design experiments to quantify metal combustion completeness, an important parameter that characterizes propulsion performance. Results show reduced energetic performance of magnesium combustion is directly related to the unavoidable occurrence of unburnt metal encapsulated in the combustion products caused by condense-luminescence. The new data provide insight into the advanced physics controlling metal particle combustion. The analyses suggest a path to improve magnesium energetic output by controlling radiative loss.